Stability of semi-markov evolution systems and its application in financial mathematics - Biirdeinyi, A. G.; Svishchuk, A. V. (Ukrains’kyi Matematychnyi Zhurnal, 1996)
We study the problem of stability of semi-Markov evolution systems and its application in financial mathematics.